2016
DOI: 10.1186/s12931-016-0473-x
|View full text |Cite
|
Sign up to set email alerts
|

Integrated safety and efficacy analysis of once-daily fluticasone furoate for the treatment of asthma

Abstract: BackgroundFluticasone furoate is a once-daily inhaled corticosteroid. This report provides an overview of safety and efficacy data that support the use of once-daily fluticasone furoate 100 μg or 200 μg in adult and adolescent asthma patients.MethodsFourteen clinical studies (six Phase II and eight Phase III) were conducted as part of the fluticasone furoate global clinical development programme in asthma. Safety data from 10 parallel-group, randomised, double-blind Phase II and III studies (including 3345 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…and controlled ileal release formulated corticosteroids (including budesonide 6.0 mg q.d.) and is expected to increase with duration of exposure 21,23,30–34 . Adrenal AEs were reported during our studies in 14.4% of participants receiving BOS 2.0 mg b.i.d., most of which did not result in discontinuation of the study drug or in clinical manifestations of adrenal insufficiency or glucocorticoid excess.…”
Section: Discussionmentioning
confidence: 56%
“…and controlled ileal release formulated corticosteroids (including budesonide 6.0 mg q.d.) and is expected to increase with duration of exposure 21,23,30–34 . Adrenal AEs were reported during our studies in 14.4% of participants receiving BOS 2.0 mg b.i.d., most of which did not result in discontinuation of the study drug or in clinical manifestations of adrenal insufficiency or glucocorticoid excess.…”
Section: Discussionmentioning
confidence: 56%
“…The benefit versus existing ICS is the once-daily dosing regimen, which is believed to improve treatment adherence. Clinical trial data from fourteen studies support the safety profile of FF and favour FF over placebo for clinical outcomes including lung function, rescue inhaler use and exacerbations [7]. In addition, high single-dose (1000 mcg) FF protects against AMP-induced bronchoconstriction within 2 h of dosing, an effect that, although diminished, was still significant 24 h later [8].…”
Section: Introductionmentioning
confidence: 88%
“…adenosine monophosphate -AMP) acting stimuli [2][3][4][5]. ICS improve lung function, lower the frequency of exacerbations and decrease symptoms [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…An integrated safety and efficacy analysis study pooled data from 14 Phase II and Phase III studies and demonstrated FF efficacy compared with placebo 44 .…”
Section: Clinical Research Studiesmentioning
confidence: 99%